EFEK GENOTOKSISITAS PADA BAHAN DENTAL ADHESIF - Izham, Andi; Auerkari, Elza Ibrahim (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 11 No 2 (2021): Indonesian Journal of Legal and Forensic Sciences, 2021)
The use of dental adhesive materials in dental practice everyday has raised questions about the biological effects on tissues. Adhesive system has attracted considerable research interest in recent years, dental adhesive will succeed depends on the chemical adhesive, on the appropriate clinical management of materials and the knowledge of morphological changes in dental tissue caused by different bonding procedures. Some studies suggest that the dental adhesive material Genotoxicity have any effect on the network. Genotoxic effects may significantly reduce the potential for tissue repair or cause the development of neoplasia in the long term.